THE ROLE OF LEGAL EDUCATION IN REFORMING THE EDUCATION SYSTEM (World Bulletin of Social Sciences, 2023)
The article reports the processes of improving the legal culture of young people. The role and significance of legal education and upbringing in the formation of the legal consciousness of an individual, as well as scientific and theoretical values